(untitled) (Journal of the College of Basic Education, 2022)
People at all levels (women and men) face an increase in fat for some parts of the body, and to overcome this problem, the researchers prepared special exercises known as (intersected exercises) that target essential parts of the body that contain fat for women ages (25-35). :-1- To identify the effect of cross-training exercises on weight reduction for aerobic trainees aged (25-35).2- To identify the effect of cross-training exercises on some biochemical variables for aerobics trainees.The most important research hypotheses were:Intersectional exercises have a positive effect on weight reduction and some biochemical variables for aerobic trainees at ages (25-35).